Prevalence and Pattern of Pain Presentation among Patients Attending a Tertiary Dental Center in a Southern Region of Nigeria - Olufemi Gbenga Omitola; Abiodun Olabisi Arigbede (Tabriz University of Medical Sciences, 2010)
Background and aims. Orofacial pain is one of the most common reasons for attendance at the dental clinic. The prevalence and the sources of orofacial pain vary from place to place and patients' response to pain also differs. The aim of this study was to determine the prevalence and pattern of orofacial pain as well as the factors influencing patients' response to orofacial pain among patients presenting for dental treatment in our center. Materials and methods. Consecutive patients presenting with orofacial pain at the Dental Center, University of Port Harcourt Teaching Hospital during the one-year period of the study were recruited into the study. Patients' demographic data were collected and recorded in special forms. Patients were later examined to confirm the specific cause of pain. This was also recorded. Data generated were analyzed using SPSS for Windows. Results. Four hundred and forty-eight patients out of the 2,426 patients seen during the study period had orofacial pain, yielding a prevalence rate of 18.5%. There were 255 females and 193 males with most patients in the 17-27-year age group (49.1%). Lower jaw was commonly affected. Most patients presented after a period of at least one month, with severe and spontaneous pain. Most patients had drug therapy before presentation. Caries was the most common source of orofacial pain. Conclusion. Orofacial pain was not uncommon in our center and it accounted for about 20% of patients' attendance in the center. Dental caries and periodontal diseases were the most common sources of orofacial pain while temporomandibular joint pain and atypical facial pain were not common in our center. Young adults and females were most commonly affected.